Формування відповідальності як поведінкової компетенції фахівця з управління проектами - Пономарьов, Олександр Семенович (НТУ "ХПІ", 2016)
Розглянуто сутність феномену відповідальності та її роль в житті й діяльності людини і суспільства. Показано, що відповідальність має розглядатися як одна з найважливіших поведінкових компетенцій фахівця з управління проектами. Проаналізовано стан проблеми з формування і розвитку відповідальності студентів, висвітлено практичний досвід її формування в процесі викладання дисципліни з поведінкових компетенцій. Показано необхідність забезпечення системної цілісності навчально-виховного процесу і застосування активних методів навчання. Запропоновано вважати відповідальність одним із складників системи поведінкових компетенцій фахівця з управління проектами.

The essence of the phenomenon of responsibility is considered. It plays an important role in the life of man and society. A sense of personal responsibility is essential for professional project management. However, with respect to the standard IPMA behavioral competencies of the specialist does not consider responsibility as a competence. This article explains the need to consider the responsibility of one of the most important behavioral competencies of project management specialists. The paper analyzes the problem of studying the phenomenon of responsibility. Examples of his studies in philosophy, psychology and pedagogy. The approaches to the formation and development of students' responsibility. Emphasized the lack of an integrated system of education accountability in higher education. Illuminated by the author's practical experience in the formation and development of responsibility in the process of teaching of the discipline "managerial competence". In particular, the standard program is supplemented with important topics of the course on the philosophy of management, psychology, management and culture management. It is shown that the effective formation of responsibility of students is necessary to ensure the integrity of the system of educational process and consistently apply active learning methods. It was stressed that the responsibility is required professionally and socially important personal characteristics of a person. This primarily relates to the project and to the members of his project team. It is proposed to include responsibility in behavioral specialist competencies in project management as one of the most important components.
Formation of responsibility as a behavioral specialist competence in project management
Keywords: поведінкові компетенції; студент; навчально-виховний процес; практична спрямованість; активні методи навчання; інноваційні педагогічні технології; responsibility; behavioral competence; project management; student; educational process; practical orientation; active learning methods; innovative educational technology